Islamic Religious Brand Community Support Practices in Encouraging Creativity Values in The Religiocentric Market of Thailand - Ritto, Daee; Sudarti, Ken (JURNAL AKTA, 2024)
The practice of supporting the Islamic Religious Brand Community in Encouraging Creativity Values in Thailand's Religiocentric Market is one effort that is worth considering in online transactions considering that in the conditions of virtual transactions there are many product choices so that consumers will find it easy to get goods according to religious criteria, especially halal and non-halal products so that consumers can compare the type and value of products with others. Through this religious brand community, consumers create a bond based on shared values. For the religiocentric market, especially in Thailand, shared religious values become a strong glue and influence consumer purchasing decisions. Support from the religious community which can be in the form of Religious Support, Emotional Support and Informational Support is an antecedent variable that is considered to form Customer Ethical Perceptions and trust which ultimately leads to their willingness to be involved in creativity in the Thai Religious Market. The concept above is value co-creation, namely value creation that involves customers as active actors in creating the value of the goods themselves. This research uses explanatory research with a quantitative approach to analyze data and test it. The research aims to determine the relationship between two or more variables regarding Islamic Religious Brand Community Support Practices in Encouraging Creativity Values in Thailand's Religious Market. The results of this research show that there is a close relationship that is mutually sustainable and influences each other between Islamic Religious Brand Community Support Practices in Encouraging Creativity Values in the Thai Religious Market which causes an increase in the economic level and welfare of the community, both producers and consumers, especially seen from the perspective of the religious community in Thailand.